Characterizing the biomechanical differences between novice and expert point‐of‐care ultrasound practitioners using a low‐cost gyroscope and accelerometer integrated sensor: A pilot study. Issue 2 (29th March 2022) - Prager, Ross; Pageau, Paul; Hodges, Timothy; Yan, Christina; Woo, Michael; Nemnom, Marie‐Joe; Millington, Scott; Holden, Matthew; St‐Gelais, Raphael; Cheung, Warren J.
Abstract: Introduction: Point‐of‐care ultrasound (POCUS) has become an important diagnostic tool in acute care medicine; however, little is known about the biomechanical differences between novice and expert practitioners. Methods: A low‐cost (50 CAD) gyroscope and accelerometer integrated sensor was assembled and affixed to an ultrasound probe. Seventeen participants, nine novices and eight experts, were recruited to perform three abdominal and four cardiac scans on a standardized patient. Participant demographics, time per scan, average acceleration, average angular velocity, decay in acceleration and angular velocity over time, and frequency of probe movements were analyzed. Video capture with blinded video review was scored. Results: On video review, experts had higher image optimization and acquisition scores for both abdominal and cardiac scans. Experts had shorter scan times for abdominal (7 s vs. 26 s, p = 0.003) and cardiac (11 s vs. 26 s, p < 0.001) scans. There was no difference in average acceleration ( g ) between novices and experts performing abdominal (1.02 vs. 1.01, p = 0.50) and cardiac (1.01 vs. 1.01, p = 0.45) scans. Experts had lower angular velocity (°/s) for abdominal scans (10.00 vs. 18.73, p < 0.001) and cardiac scans (15.61 vs. 20.33, p = 0.02) There was a greater decay in acceleration over time for experts performing cardiac scans compared to novices (−0.194 vs. −0.050, p = 0.03) but not for abdominal scans or when measuring angular velocity. The frequency of movements (Hz) was higher for novices compared to experts for abdominal (16.68 vs. 13.79, p < 0.001) and cardiac (17.60 vs. 13.63, p = 0.002) scans. Discussion: This study supports the feasibility of a low‐cost gyroscope and accelerometer integrated sensor to quantify the biomechanics of POCUS. It may also support the concept of "window shopping" as a method by which experts obtain abdominal and cardiac views, where sliding is used to find an acoustic window, then smaller rocking and tilting probe movements are used to refine the image.